Effect of Rehydration on the Performance of Mechanically Loaded UHPC - Wang, Yue; An, Mingzhe; Lu, Jing; Huang, Hanfeng (Frontiers in Materials, 2022)
Unhydrated cementitious materials in ultrahigh-performance concrete (UHPC) with a low water-to-binder ratio stop hydrating owing to water shortage but can continue to hydrate after re-exposure to water; this phenomenon is referred to as rehydration. This article discusses the effects of rehydration on the performance of mechanically loaded UHPC when subjected to continuous water exposure. For this purpose, UHPCs with a steel fiber content of 0 and 2% were prepared with a constant water–binder ratio of 0.20. A uniaxial compression load was applied to generate microcracks in the UHPC, where cube specimens were preloaded up to 50, 70, 90, and 100% of the ultimate compressive load. After preloading, UHPC specimens were stored in water for 90 days. Preloading is found to have a more significant effect on the splitting tensile strength than on the compressive strength. At different preload levels, the splitting tensile strength first increases and then decreases with increasing water curing time. The cumulative capillary water absorption decreases with increasing water curing time, and the percentage decrease increases with an increasing preload level. The chemically bound water content increases with increasing water curing time, and the increase becomes more significant at a higher preload level. The filling effect of the rehydration reduces the connectivity of the internal pores, which is the main reason for the increase in strength and decrease in permeability observed under water curing. These results provide a foundation for the application and life-cycle design of UHPC structures over long service periods in water environments.